PENDEKATAN GENDER DALAM ISLAM PERSPEKTIF SACHIKO MURATA - Afifah Afifah (Sekolah Tinggi Agama Islam Taruna Surabaya, 2023)
Sachiko Murata in gender issues uses arguments based on the approach of the theory of the universe (cosmology) as the basis of his thinking and more towards the textual (mystical) with